The relationship between stress management skills and student resilience in collaborative project-based assessment - Uli Uli; Edi Istiyono; Farida Agus Setiawati; Ghany Desty Laksita (Graduate School, Universitas Negeri Yogyakarta, 2025)
This study aims to examine the relationship between stress management skills and students’ resilience in facing collaborative project-based assessment. The participants were 117 junior high school students from two private schools in Bandung who were involved in collaborative project-based assessments. This study employed a quantitative correlational research design. Data were collected using questionnaires measuring students’ stress management skills and resilience, which were validated through expert judgment and tested for reliability using Cronbach’s Alpha. The data were analyzed using descriptive statistics and Spearman’s correlation test. The results show that most students demonstrate high levels of stress management and resilience, indicating the use of adaptive coping strategies and strong learning perseverance. However, the correlation between stress management and resilience was very weak and not statistically significant. These findings indicate that students’ academic resilience may be influenced more by external factors such as social support, learning environment, and academic context rather than individual stress management skills. This study highlights the importance of supportive learning environments in strengthening students’ resilience when facing collaborative project-based assessments.